Correr com rinocerontes - Baldi, Cristiano Ordovás (2015)
This work falls within the Creative Writing area and comprehend a fictional and a reflexive essay. Narrated by its protagonist, the novel “Correr com Rinocerontes” investigates the life of an intellectualized and enlightened family living in Porto Alegre city, whose life and relations were drastically changed after a violent accident involving one of its members. The brief essay accompanying the novel exposes elements of the genesis of the work and seeks to relate memories, memory and choice of narrative voice.